DETERMINAN KEBIJAKAN HUTANG DENGAN DIMODERASI KEUNIKAN PRODUK: Akuntansi - Hasan Mukhibad; Razaq Noor Muhammad Noor Muhammad (SUBSTANSI, 2021)
The purpose of this study was to examine the effect of financial flexibility, tangibility assets, and tax shields on debt policy with product uniqueness as a moderating variable. The population in this study are various industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 as many as 213 companies. The sampling technique was purposive sampling, in order to obtain 145 units of analysis. The data analysis method of this research is panel data regression analysis and moderating regression analysis with the selected research model being the fixed effect model (FEM) for panel data regression analysis and the random effect model (REM) for moderating regression analysis. The selection of the data analysis method was based on the results of the hausman test. The test results show that financial flexibility has a negative effect on debt policy, and tangibility assets has a significant positive effect on debt policy. Then, the uniqueness of the product is able to moderate the effect of financial flexibility and tangibility assets on debt policy. However, tax shields have no effect on debt policy and product uniqueness is unable to moderate the effect of tax shields on debt policy.